Perilaku Pemilih Etnik Aceh Dalam Pemilihan Kepala Daerah 2017 Kabupaten Aceh Barat Daya - Robbi Sugara; Pujiati Pujiati; Ichwan Azhari (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This paper aims to find out about the behavior of Acehnese ethnic voters in determining regional head candidates in accordance with the expectations of voters and the form of strategies used by regional head candidates in gaining sympathy from the people of Southwest Aceh. This research uses ethnographic methods. Research techniques with in-depth interviews and participatory observation of campaign teams, leaders and the community in the implementation of the 2017 elections. From the results of the study, the community chose regional head candidates based on vision and mission related to social welfare such as, empowering farming communities by cutting seed and fertilizer prices, or scholarships for underprivileged children. In getting the voices of the people of Southwest Aceh, prospective regional heads have strategies using cultural symbols such as traditional clothing, meukotop skullcaps, rencong, agamai and post bases. Then the candidates also make use of community groups such as the Koran and youth communities. With a strategy approach to cultural symbols and community groups, the candidates hope to gain the voice of the community and be able to provide knowledge to the younger generation about awareness of the cultural values of Aceh in the Southwest Aceh District.